A rare presentation of ovarian fibrothecoma in a middle age female: case report - Obeidat RA; Aleshawi AJ; Obeidat HA; Al Bashir SM (Dove Medical Press, 2019)
Rawan A Obeidat,1 Abdelwahab J Aleshawi,2 Hasan A Obeidat,2 Samir M Al Bashir3 1Department of Obstetrics & Gynecology, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of General Surgery and Urology, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 3Department of Pathology, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan Abstract: Fibromas/fibrothecomas are considered to be benign ovarian tumors. We describe a rare case of recurrent fibrothecoma with a clinically malignant course. A 42-year-old woman, with no family history of malignancy, operated multiple times for tumor that recurred three times within 4 years despite radical surgical removal. Initially, she presented with 9×7×10 cm right ovarian mass, frozen section was consistent with fibrothecoma and thus right salpingoophorectomy was performed. At the last two recurrences, she was found to have recurrent multiple abdomino-pelvic fibrothecomas and two long major operations were performed. This malignant behavior of a benign tumor is very rare. Further genetic analysis and immunohistochemistry studies are recommended to be conducted. Furthermore, new modalities of treatment should be considered, eg, high-intensity focused ultrasound and/or hormonal treatment. Keywords: recurrent fibrothecoma, ovarian tumor, radical surgery, sex cord-stromal tumors